A step back: rethinking the usefulness and effects of escalation clauses in international arbitration - Gutierrez Lucar, Marcial Giovanni (2025)
In this paper you will find the identification of the main disadvantages of agreeing to a staggered arbitration clause, as well as the tools available to us in international arbitration so that the arbitration phase is not avoided. Likewise, there are proposals to take into consideration when agreeing these clauses, in order to promote that the parties settle their disputes instead of having a third party do it. Translated with DeepL.com (free version)